A voz da criança na poesia infantil brasileira - Azevedo, Sandrelle Rodrigues de (2023)
This thesis analyzes the presence of the child's voice in Brazilian children's poetry, taking as a starting point the work Poesias Crianças, by Olavo Bilac, published in 1904, to the contemporary production of poems for children, in a selection of 100 books to which we had access during the search. We initially bring an account of the changes in the way childhood was seen in the West over time, based on the studies of Ariès (1981), Gélis (1991) and Perrotti (1986), as well as their specificities in Brazilian soil, studied by Priore ( 2007) and Dourado and Fernandes (1999), and the consequences of this “discovery” of childhood by the human sciences, supported by Gouvêa (2011) and Souza (1997). We also present how Brazilian literature written for children emerges, mainly from the point of view of narratives, and we comment on how this look at childhood can also be studied from the literary text, based on Zilberman (1987), Lajolo and Zilberman (2002) and Coelho (2006, 2010). Then, we arrive at the specificities of national poetry aimed at children, and make a historical journey of the appearance and developments of children's poetic production in Brazil, dialoguing with Bordini (1986, 1989), Coelho (2006), Cecantinni and Aguiar (2012), Camargo (2000, 2012) among others. Next, we bring the main quantitative results of the analysis of our corpus, and outline the criteria for defining our categories of analysis. In the last chapter, we look in depth at some complete poetic works, focusing on the voices that appear in the texts and their relationship with aesthetic quality, production period, pedagogical character and child representativeness. Finally, we conclude that although it is important for a possible identification of the reader with the poetic text, the lyrical subject is just one of the resources that can be used by authors of poems to produce a text in verses of quality for children.